Pemanfaatan Cloud Computing Dalam Manajemen Penyimpanan Data Di SMK Swasta Ira Medan - Dody Hidayat; B Bud; Ika Sari (Jurnal TUNAS, 2021)
Community service is one of the pillars in the Tridarma of Higher Education so that every lecturer is obliged to carry out. Through service, it is hoped that lecturers can share their knowledge directly with the community (outside the academic community) with the hope that the community can directly enjoy the existence of the College. In connection with this, the Informatics Management Study Program sent several lecturers and students to do service at the Ira Medan Vocational School. The topic of service is utilizing cloud computing data storage among students. This is done considering that as students they must have done internet-based data storage by utilizing computerized technology through the features of gmail, facebook, google drive, dropbox, icloud, and so on. Considering that currently web features are increasingly dominating the world in the millenial 4.0 century, the use of gmail, facebook, google drive, dropbox, icloud features is very much needed. Many people can use the internet, but not many also know how to apply the benefits of cloud computing by utilizing the features contained in it. Utilization of maximum features can help simplify and speed up storing the data. Considering the large number of students and limited space and time, this training was conducted specifically for class XII students. It is hoped that with this training, a minimum of 50% (fifty percent) of the training participants can understand this cloud computing service to the fullest.